CHAPTER 1 - THE RELATIONS BETWEEN MUSEOLOGY AND COMMUNITY DEVELOPMENT: SOCIETY CHANGES, MUSEOLOGY CHANGES - Dos Santos, Paula Assunção (Edições Universitárias Lusófonas, 2009)
Much has been written about the critical atmosphere experienced in the 60’s, when struggles for social justice, civil rights, individual freedom, world peace and democracy set a tune of change in society. Episodes such as the students mobilizations in Europe (which have in the May of 68 its celebrated climax), the hippie movement in USA, the voices against dictatorships in Latin America and countries from the Iberian Peninsula; and names such as Nelson Mandela and Martin Luther King, among others, marked a decade of non-conformism and became to cast new social goals worldwide. It is not by chance that the 60s also brought radical changes to the field of museology as a whole. From the reassessment of purpose and relevance of museology for society to the re-evaluation of effectiveness of the classic museum functions, transformations were profuse in “the traditionally stable and conservative museum world.